Stereoselective synthesis of trans-fused iridoid lactones and their identification in the parasitoid wasp Alloxysta victrix, Part II: Iridomyrmecins - Hilgraf, Robert; Zimmermann, Nicole; Lehmann, Lutz; Tröger, Armin; Francke, Wittko (Beilstein Journal of Organic Chemistry, 2012)
Following our earlier approach to the synthesis of dihydronepetalactones, all eight stereoisomers of trans-fused iridomyrmecins were synthesized starting from the enantiomers of limonene. Combined gas chromatography and mass spectrometry including enantioselective gas chromatography revealed that volatiles released by the endohyperparasitoid wasp Alloxysta victrix contain (4S,4aR,7S,7aR)-iridomyrmecin of 95–97% ee and stereochemically pure (4S,4aS,7R,7aS)-iridomyrmecin as a minor component.
Keywords: Alloxysta victrix; identification; iridoid; stereoselective synthesis; trans-fused iridomyrmecin